4x^2-17x+11=-4x+2

Simple and best practice solution for 4x^2-17x+11=-4x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x^2-17x+11=-4x+2 equation:


Simplifying
4x2 + -17x + 11 = -4x + 2

Reorder the terms:
11 + -17x + 4x2 = -4x + 2

Reorder the terms:
11 + -17x + 4x2 = 2 + -4x

Solving
11 + -17x + 4x2 = 2 + -4x

Solving for variable 'x'.

Reorder the terms:
11 + -2 + -17x + 4x + 4x2 = 2 + -4x + -2 + 4x

Combine like terms: 11 + -2 = 9
9 + -17x + 4x + 4x2 = 2 + -4x + -2 + 4x

Combine like terms: -17x + 4x = -13x
9 + -13x + 4x2 = 2 + -4x + -2 + 4x

Reorder the terms:
9 + -13x + 4x2 = 2 + -2 + -4x + 4x

Combine like terms: 2 + -2 = 0
9 + -13x + 4x2 = 0 + -4x + 4x
9 + -13x + 4x2 = -4x + 4x

Combine like terms: -4x + 4x = 0
9 + -13x + 4x2 = 0

Factor a trinomial.
(1 + -1x)(9 + -4x) = 0

Subproblem 1

Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1

Subproblem 2

Set the factor '(9 + -4x)' equal to zero and attempt to solve: Simplifying 9 + -4x = 0 Solving 9 + -4x = 0 Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -4x = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -4x = 0 + -9 -4x = 0 + -9 Combine like terms: 0 + -9 = -9 -4x = -9 Divide each side by '-4'. x = 2.25 Simplifying x = 2.25

Solution

x = {1, 2.25}

You can always share this solution

See similar equations:

| -8+6f=3f+10 | | 4x-3+x=52 | | -1.2(-1.3t)= | | 200=40x-90 | | 10-4r=-4r+10 | | 6(-5u+1)= | | 8x+50+(-5x)+34=90 | | ln(x)=(x^2)+1 | | -3+(v+4)= | | -1+3d=6+2d | | (3z)(-8)= | | 7/9k=5/15 | | -4(-6+7r)= | | w+-8=0 | | 2(12-k)-(k+2)=8(2-3k)-3(5-6k) | | 5x+650=5 | | 6+x=97 | | -5t+7t=h(t) | | 1+10g=-8+10g | | 6(-7+2d)= | | 15x-25=65 | | -1+(m+-4)= | | -9s=7-9s | | -5-6t=-6t-3 | | 3x+36=2x-45 | | -16t^2+940=h | | 20-305=65-40x | | -16t^2+1000=h | | 7+2z=3z | | 4/9=/63 | | -3(-4-2)=7 | | 200x+35=2-45 | | 160.00+0.85(1600)= | | -5j=-6-3j | | 4x+20=2x+66 | | 20=20x-90 | | 20=20x-9 | | -5b+b=-4b | | 9(2x+4)=18 | | -16t^2+1700=h | | 0.21(380)+41= | | -5(w+2)-w-3=-6(w+5)+17 | | 100x/5x | | 1-x/x | | 555-20x=5y | | 150x-5x=65 | | (1/4x)-8=4 | | 80cl=ml | | 2x-350=65-4x | | 80cl= | | 2/8x8 | | 16-6=x/4 | | 20x+35=5y-45 | | 6(3-2x)=56 | | 2y+2=4x+6 | | 2*3.14159265*x=14 | | 200+10x=20x-90 | | X^3+2xy+y^3=0 | | 6+5x+350=11y | | 9y-(-8)=-16 | | -2(-8x-1)=-28+6x | | 150x-50=650 | | 1+2x+x=13 | | 4v^3-5v^2+4v-5=0 | | x^3+1=28 |

Equations solver categories